If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + 38 = -5m + -16 Reorder the terms: 38 + 7m = -5m + -16 Reorder the terms: 38 + 7m = -16 + -5m Solving 38 + 7m = -16 + -5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5m' to each side of the equation. 38 + 7m + 5m = -16 + -5m + 5m Combine like terms: 7m + 5m = 12m 38 + 12m = -16 + -5m + 5m Combine like terms: -5m + 5m = 0 38 + 12m = -16 + 0 38 + 12m = -16 Add '-38' to each side of the equation. 38 + -38 + 12m = -16 + -38 Combine like terms: 38 + -38 = 0 0 + 12m = -16 + -38 12m = -16 + -38 Combine like terms: -16 + -38 = -54 12m = -54 Divide each side by '12'. m = -4.5 Simplifying m = -4.5
| 6x=208-4(52+-1.5x) | | 5x-1=6x-5 | | 3a-5=-6 | | -2(2+w)=-20 | | -15=6g-3 | | 50x+3=7 | | 42=6x+7 | | x/3-2=5 | | 4(q-5)=16 | | 8a+10b=6 | | 2Y^2+9Y-5= | | 4y=208-6x | | x^3-6x^2+16X=96 | | 2(3x-4)=28 | | 0.5x-1.5=2.5 | | 5.4+-3(4m+3)=45.7 | | 6x+14x=16 | | 2(3x+7)-(x-4)= | | -6y+15=-9 | | -6+3y/5=3 | | -2(5)+2=5y-1 | | 3(4y-7)=6 | | 8(x+3)=10(x+7) | | (-2)(-7)=14 | | 9(5x-2)=17 | | 2a/5+5=1 | | (6x+2)+(4x+8)= | | k/5-6=2 | | 2-3c=-7 | | 8x=10-11x | | 2n/3+5=7 | | 7x+2=20+3x+8 |